2018
DOI: 10.3390/molecules23102510
|View full text |Cite
|
Sign up to set email alerts
|

New Layered Polythiophene-Silica Composite Through the Self-Assembly and Polymerization of Thiophene-Based Silylated Molecular Precursors

Abstract: A new layered hybrid polythiophene-silica material was obtained directly by hydrolysis and polycondensation (sol-gel) of a silylated-thiophene bifunctional precursor, and its subsequent oxidative polymerization by FeCl3. This precursor was judiciously designed to guarantee its self-assembly and the formation of a lamellar polymer-silica structure, exploiting the cooperative effect between the hydrogen bonding interactions, originating from the ureido groups and the π-stacking interactions between the thiophene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In previous studies, the formation of ordered domains in the amorphous structure of hybrid silicon xerogels was evidenced by: (i) a signal in the X-ray diffraction spectra at 2θ < 10°, (ii) the appearance in the NMR spectra of T 2,3 structures (T n , notation used for silicon atoms bonded to three oxygen atoms and Q n , for silicon atoms bonded to four bridged oxygen atoms) [ 30 , 31 ], and (iii) a band at around 1150 cm −1 in the Fourier-transform infrared spectroscopy (FTIR) spectra [ 20 , 21 , 22 ]. These observations are consistent with data obtained by mass spectrometry (MS) [ 21 ], simulations of the FTIR spectra, and inelastic neutron spectroscopy (INS).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the formation of ordered domains in the amorphous structure of hybrid silicon xerogels was evidenced by: (i) a signal in the X-ray diffraction spectra at 2θ < 10°, (ii) the appearance in the NMR spectra of T 2,3 structures (T n , notation used for silicon atoms bonded to three oxygen atoms and Q n , for silicon atoms bonded to four bridged oxygen atoms) [ 30 , 31 ], and (iii) a band at around 1150 cm −1 in the Fourier-transform infrared spectroscopy (FTIR) spectra [ 20 , 21 , 22 ]. These observations are consistent with data obtained by mass spectrometry (MS) [ 21 ], simulations of the FTIR spectra, and inelastic neutron spectroscopy (INS).…”
Section: Introductionmentioning
confidence: 99%
“…Mehdi, Clément et al showed that optical properties of polythiophene embedded in a silica matrix could be controlled by polymerizing of the inorganic part of mono-silylated-thiophene precursor [8]. The crosslinking in water was assisted by self-assembly through van der Waals interactions of alkylene chains, π-stacking interactions between the thiophene units, and hydrogen bonding interactions between ureido groups.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Thiophene derivatives are versatile and key constituents of many organic semiconducting materials. , It has already been demonstrated that the supramolecular features of these building blocks can be translated at the macromolecular level to govern the organization of corresponding unit-containing polymers. , With this in mind, we decided to investigate the supramolecular organization of modified thiophene with the groups prone to interact by halogen bonding . Several studies have already reported the X-ray structures of halogen-bonded arrays based on brominated thiophenes at positions 2 and/or 5, along with other bromine-containing analogues .…”
Section: Introductionmentioning
confidence: 99%